We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
339
1
avatar

how do you solve it?

 Jun 26, 2018

Best Answer 

 #1
avatar+28179 
+2

First, divide each term by 2 to get:

 

x2 + 3x - 40 = 0

 

Then factor this to get:

 

(x - 5)(x + 8) = 0

 

So the possible solutions are: x = 5 and x = -8

.

 Jun 26, 2018
 #1
avatar+28179 
+2
Best Answer

First, divide each term by 2 to get:

 

x2 + 3x - 40 = 0

 

Then factor this to get:

 

(x - 5)(x + 8) = 0

 

So the possible solutions are: x = 5 and x = -8

.

Alan Jun 26, 2018

28 Online Users

avatar